Computed tomography in veterinary medicine: currently published and tomorrow’s vision - Keane, Matthew; Paul, Emily; Sturrock, Craig; Rauch, Cyril; Rutland, Catrin S. (InTechOpen, 2017)
The utilisation of Computed Tomography (CT) in veterinary practice has been increasing rapidly in line with reduced cost, improved availability and the increase in expertise and technology. This review briefly examines the recent technological advancements in imaging in the veterinary sector, and explores how CT and micro-CT (μCT) have furthered basic understanding and knowledge, and influenced clinical practice and medicine. The uses of CT technology in veterinary research, especially in relation to bone, vasculature and soft tissues, are explored and compared in relation to the different species. CT is essential not only for the diagnosis and treatment of many disorders, but it is now being used to understand areas ranging from drug delivery and surgical advancements through to anatomical and educational uses throughout the world.